Memory sites and generational agencies: Site, space and experience - Sepúlveda Galeas, Mauricio; Sepúlveda Gatica, Andrea; Piper Shafir, Isabel; Troncoso Pérez, Lelya (Última Década, 2020)
In this article we analyze the interaction of young people born in postdictatorship from two memory sites, Londres 38 and Villa Grimaldi, both former torture centers during the Chilean dictatorship (1973-1990). Audiovisual recordings of these interactions were analyzed and from this analysis we suggest that the experience enables the expansion and coordination of knowledge, emotions, perceptions, imagination and memories, bringing disputes over the significance of the recent past between generations into tension, depending on their approach to this past. Finally, we reflect on the importance of positioning young people as constructors of memories of the recent past.